Best Practices in Technical Education Programme for Students' Capacity Building and Sustainable Development in the 21st Century - Oviawe, Jane Itohan; Uwameiye, Raymond; Uddin, Patrick S.O. (Journal of Technical Education and Training, 2017)
The purpose of this study is to determine the best practices in technical education programme for students' capacity building and sustainable development in the 21st century using survey research design. The entire population of 50 technical teacher educators in the Departments of Vocational and Technical Education in the three public universities in Edo and Delta States of Nigeria was used for this study. The instrument used for data collection is a 57-item questionnaire, with a five point Likert scale. The data collected were analysed using mean statistics. The findings revealed that there were almost no joint programme in technical education between school and industries except for the Students' Industrial Work Experience Scheme (SIWES). There is also no involvement of industries in the running of technical education programme in Nigeria. Some challenges to effective school-industry collaboration and some ways that schools and industries could jointly engage to enhance students' capacity building in technical education were identified. It was recommended among others that educational institutions offering technical education programmes should tap the dynamisms and synergies of the 21st century workplace to the full to produce technical education graduates who can fit in and succeed in the 21st century world of work.